2005
DOI: 10.1073/pnas.0506679102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SR-BI protein levels by phosphorylation of its associated protein, PDZK1

Abstract: Scavenger receptor class B type I (SR-BI) is a high-density lipoprotein (HDL) receptor that mediates the selective uptake of HDL cholesterol and cholesterol secretion into bile in the liver. Previously, we identified an SR-BI-associated protein, termed PDZK1, from rat liver membrane extracts. PDZK1 contains four PSD-95͞ Dlg͞ZO-1 (PDZ) domains, the first of which in the N-terminal region is responsible for the association with SR-BI. PDZK1 controls hepatic SR-BI expression in a posttranscriptional fashion both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 36 publications
(47 reference statements)
2
44
2
2
Order By: Relevance
“…endocrine) seem to influence the relationship of NHERF proteins with their substrates. Phosphorylation of NHERF3 at Ser 509 by PKA and glucagon was associated with increased expression of the scavenger receptor class B type I and PDZK1, which resulted in decreased plasma high density lipoprotein levels (50). Although the details responsible for NHERF3-dependent regulation of NHE3 activity remain to be determined, the results of the current study appear to represent another example of the highly regulated association of the NHERFs with their ligands.…”
Section: Discussionmentioning
confidence: 79%
“…endocrine) seem to influence the relationship of NHERF proteins with their substrates. Phosphorylation of NHERF3 at Ser 509 by PKA and glucagon was associated with increased expression of the scavenger receptor class B type I and PDZK1, which resulted in decreased plasma high density lipoprotein levels (50). Although the details responsible for NHERF3-dependent regulation of NHE3 activity remain to be determined, the results of the current study appear to represent another example of the highly regulated association of the NHERFs with their ligands.…”
Section: Discussionmentioning
confidence: 79%
“…It seems likely that these other regions of PDZK1 interact with additional cellular components to properly control SR-BI activity. It is possible that the phosphorylated C terminus of PDZK1 (35) or the other three PDZ domains (PDZ2-PDZ4) and their binding partners may play a critical role in regulating SR-BI. Additional putative PDZK1-interacting components apparently are either not present in limiting amounts or cannot interact with PDZK1 efficiently unless it is bound to SR-BI, because overexpression of PDZK1 protein in the liver of WT mice had virtually no effect on normal hepatic SR-BI levels and lipoprotein metabolism (no dominant negative phenotypes observed; the excess PDZK1 did not titrate out other critical components).…”
Section: Discussionmentioning
confidence: 99%
“…The role(s) of these domains in the regulation of hepatic SR-BI are unknown. Nakamura et al (35) have shown that the C terminus and the phosphorylation of PDZK1 are required for optimal PDZK1 transgene-mediated induction of increased SR-BI protein levels in cultured cells. It is possible that PDZ2, PDZ3, and/or PDZ4 bind to other, as yet unidentified, cellular components involved in SR-BI regulation.…”
mentioning
confidence: 99%
“…It is well known that CEs, in specialized tissues such as the adrenal cortex and liver ( 56 ), are taken up directly from HDLs ( 57 ) by a plasma-membrane scavenger receptor protein (SR-B1) in rodents ( 49 ), and CLA-1 in humans ( 58 ). Furthermore, a selective uptake of CE-HDLs by SR-B1 has been described in rapidly proliferating tumor cells ( 50,58,59 ).…”
Section: Discussionmentioning
confidence: 99%